Comparison of whole body bone mineral density measurements between dual energy X-ray absorptiometry and novel bioelectrical impedance analysis - Chih-Lin Chuang; Chung-Liang Lai; Ai-Chun Huang; Po-Hua Su; Lee-Ping Chu; Kuen-Chang Hsieh; Hsueh-Kuan Lu (Scientific Reports)
Abstract Bone mineral density (BMD) is a crucial indicator of osteoporosis. Bioelectrical impedance analysis (BIA) introduces a new method for assessing body composition, specifically BMD measurement. Compared with existing ultrasound and dual-energy X-ray absorptiometry for BMD screening and diagnosis, BIA has the advantages of safety, convenience and speed. However, the accuracy of BIA for BMD measurement needs to be explored. This study aimed to evaluate the accuracy of the novel BIA technique in conducting whole-body BMD assessments in the general population of Taiwan. Overall, 318 healthy adults in Taiwan (37.67 ± 19.44 years of age; 145 male and 173 female patients) were included. Whole-body BMD was measured via foot-to-foot BIA-StarBIA-201 (StarBIA Meditek Co. LTD, Taichung, Taiwan) and the dual-energy X-ray absorptiometry (DXA) Lunar Prodigy technology (GE Medical Systems, Madison, WI, USA). Linear regression analysis, Pearson’s correlation coefficient, the Bland–Altman plot, and paired t tests were used. The whole-body BMDs measured by BIA and DXA were 1.139 ± 0.124 g/cm2 and 1.202 ± 0.168 g/cm2, respectively. The regression equation was y = 1.057x + 0.063. The Pearson correlation coefficient, mean difference, and limits of agreement were r = 0.737, − 0.053 g/cm2, and − 0.290–0.165 g/cm2, respectively. The regression equation was y = 1.057x + 0.063. The Pearson correlation coefficient, mean difference, and limits of agreement were r = 0.737 (p < 0.001), − 0.053 g/cm2, and − 0.290–0.165 g/cm2, respectively. Standing BIA was correlated with the DXA gold standard for estimating whole-body BMD in adults; however, its interchangeability remains limited. The potential bias in the measurement results of this study represents a current challenge with BIA compared with that of DXA, and there is still room for improvement. The convenient BIA method for measuring whole-body BMD may be useful in the application of primary screening and future development of BMD assessment methods. BIA is widely used to measure body composition, but its application to the measurement of BMD represents a novel technological breakthrough.